Avoiding hemodialysis access–induced distal ischemia. Issue 5 (September 2021) - Horst, Vernon D; Nelson, Peter R; Mallios, Alexandros; Kempe, Kelly; Pandit, Viraj; Kim, Hyein; Jennings, William C
Timely creation and maintenance of a safe and reliable vascular access is essential for hemodialysis patients with end-stage renal disease. Hemodialysis access–induced distal ischemia (HAIDI) is a recognized complication of arteriovenous fistulas and grafts that may result in serious or even devastating consequences. Avoiding such complications is clearly preferred over treatment of HAIDI once established. Proper recognition of patients at increased risk of HAIDI includes careful pre-operative evaluation of the patient's medical and surgical history along with physical examination and imaging to determine a plan for creating a functional permanent access while minimizing the risk of distal ischemia. Our aim is to review identifying characteristics of individuals at risk of HAIDI and provide recommendations regarding pre-operative assessment. Vascular access options and techniques are suggested for establishing a functional vascular access without distal ischemia for such patients.